What drives the performance of Swedish lower secondary schools? - André, Christophe (OECD Publishing, 2019)
This paper presents the econometric analysis of lower secondary school performance carried out for the chapter on education of the 2019 OECD Economic Survey of Sweden. The dataset covers most Swedish schools providing education for 9th graders. Student socio-economic background has a considerable impact on academic results. Policy inputs are also correlated with results, notably in schools with pupils from weaker socio-economic backgrounds, but teacher qualifications and spending per student are endogenous. For-profit private schools underperform compared to non-profit and public schools, albeit with strong heterogeneity between schools. The introduction of an indicator of competition, based on the density of schools, suggests that intensified school competition lowers results in schools with a high share of pupils from weaker socio-economic backgrounds. Schools, and especially those achieving weaker results, have scope to raise their performance by improving their adaptation to student needs. This Working Paper relates to the 2019 OECD Economic Survey of Sweden http://www.oecd.org/economy/sweden-economic-snapshot
Keywords: Education; Economics; Sweden